Endocarditis Caused by Nontypeable Streptococcus pneumoniae . (2nd February 2022) - Henriet, Stefanie S V; Langereis, Jeroen D; Lo, Stephanie W; Bentley, Stephen; Mesman, Rob J; Fejzic, Zina; van Niftrik, Laura; van Sorge, Nina M; Wertheim, Heiman F L; de Jonge, Marien I; Cremers, Amelieke J H
Abstract: The Streptococcus pneumoniae capsule is regarded as indispensable in bacteremia. We report an infant with a ventricular septal defect and infective endocarditis caused by nontypeable S. pneumoniae . In-depth investigation confirmed a deficient capsule yet favored pneumococcal fitness for causing infective endocarditis, rather than a host immune disorder, as the cause of infective endocarditis in this case.